Perovskite Nano‐Heterojunctions: Synthesis, Structures, Properties, Challenges, and Prospects. Issue 1 (9th September 2020) - Xu, Xiangxing; Wang, Xun
Abstract : Scientific and industrial interest on perovskite semiconductor materials has grown rapidly in recent years. Through the efforts of researchers professionals in chemistry, physics, materials and electronics, etc., many records based on perovskites have been and are being refreshed. The brilliant performances emerge not only from the excellent properties of perovskite themselves, but also originate from the composite material systems of hybridizing perovskites with heteromaterials. Herein, first, the crystal and nanostructures of perovskite materials, semiconductor‐based heterojunctions, and the categories of perovskite heterojunction are fundamentally introduced. Then, the state‐of‐the‐art synthesis methods, size and structure control, electron structure‐related physical properties, and applications of the perovskite‐based nano‐heterojunctions are comprehensively reviewed. Finally, perspectives on tackling challenges and developing trends are discussed. Abstract : The state‐of‐the‐art perovskite semiconductor‐based heterojunctions, especially composed of nanomaterials, are reviewed. It focuses on the categorization of the perovskite composite material systems, controllable preparation methods toward heterojunctions with various dimension combinations, morphologies and electron structures, as well as the perspectives on tackling challenges in the synthesis, assembly, characterization, and applications of perovskite nano‐heterojunctions.